Pengaruh Pelatihan Kerja, Beban Kerja dan Motivasi Kerja terhadap Kinerja Karyawan di Kantor KSP Balo’ta Kabupaten Tana Toraja - Andy Saputra Pakiding; Dwibin Kannapadang; Jens Batara Marewa (Universitas Kristen Indonesia Toraja, 2025)
This study aims to determine whether there is an effect of job training, workload, and work motivation on employee performance at KSP Balo’ta, Tana Toraja Regency. The data collection procedures in this study included interviews, questionnaires, and documentation. The research employed a quantitative method using multiple linear regression analysis, which was processed using SPSS version 23. The sampling technique used was the census (total sampling) method, in which all members of the population were included as samples, totaling 38 respondents. The results of the study indicate that: (1) partially, job training has a significant effect on employee performance. This is evidenced by the t-test results, where the significance value is 0.000 < 0.05 and the calculated t-value is −9.613 > t-table value of 1.691, indicating that variable X1 influences variable Y. (2) workload has a significant effect on employee performance, as shown by the t-test results with a significance value of 0.004 < 0.05 and a calculated t-value of 1.842 > t-table value of 1.691, indicating that variable X2 affects variable Y. (3) work motivation has a significant effect on employee performance, as evidenced by the t-test results with a significance value of 0.000 < 0.05 and a calculated t-value of 4.694 > t-table value of 1.691, indicating that variable X3 influences variable Y. (4) simultaneously, job training, workload, and work motivation have a significant effect on employee performance. This is supported by the F-test results, where the significance value is 0.000 < 0.05 and the calculated F-value is 37.209 > F-table value of 2.883, indicating that variables X1, X2, and X3 simultaneously influence variable Y.